Parametrial hematoma following fetal craniotomy and curettage in intrauterine fetal death: a case report - Ida Bagus Yudhistira Anantasurya Vidhisvara; Ida Bagus Putu Widiarsa; Margaret Gabriele Helena; I Putu Ivan Cahya Himawan (DiscoverSys Inc., 2021)
Background: Parametrial hematoma is collection of blood located in the parametrial area, which is a type of hematoma that can occur in the pelvic cavity. Postpartum hematoma is a rare but life-threatening complication of childbirth. Common risk factors to developing parametrial hematomas include multiple pregnancies, traumatic deliveries, operative vaginal delivery, prolonged labour, manual removal of placenta, inadequate hemostasis at Caesarean section, pre-eclampsia, and anticoagulation therapy. We reported a rare case of parametrial hematoma post-craniotomy and curettage of a fetus with intrauterine fetal death (IUFD) in a 28-year-old pregnant woman 24 weeks into her fourth pregnancy. Case report: A pregnant woman with 24 weeks gestation age came to emergency room with complaints of abdominal pain and bloody discharge without clear fluids 9 hours prior. She was diagnosed with preterm delivery and was given tocolytic. The following day, ultrasound examination was done and fetal heart rate (FHR) was not found, suggesting an intrauterine fetal death (IUFD). Termination was carried out with oxytocin induction but due to maternal exhaustion, pain, and lack of cooperation, a craniotomy was done in operating room followed by curettage. Twenty-four hours after curettage, patient complained of an acute lower right abdominal pain and ultrasound showed a complex mass in right adnexa measuring 8 x 8 cm, suggesting a right adnexal hematoma with a differential diagnosis of a right tubo-ovarian abscess. The patient’s haemoglobin was found to decrease to 6.0 g/dl. A laparotomy was performed and a hematoma was found in the right parametrium without active bleeding. Conclusion: Parametrial hematoma is a rare disease that can occur due to trauma (in labor) or spontaneously due to abnormalities of the uterine arteries that supply blood to the uterus. The patient present in this case report had acute abdominal pain with decreased haemoglobin without signs of bleeding after an operative vaginal birth which may or may not be the cause of the parametrial hematoma due to limitations of examination on the patients. Further observation of similar cases will be required to determine the association between parametrial hematoma and operative vaginal birth.